MORPHOLOGICAL CHANGES OF SPINAL NODES AT PHYSICAL LOADING ON A BACKGROUND PRELIMINARY OF HYPOKYNESIA - Popel, S.L. (World of Medicine and Biology, 2012)
In the experiment it is shown on laboratory rats, that the term of normalization of component components of spinal node after hypokynesia depends on multiple of influencing of the physical loading. Forming of of long duration structural track of adaptation is related to the early and expressly expressed reaction of blood vessels spinal nodes.
Keywords: spinal nodes; neuron; glyocytes; blood vessels